HD152786: A LITHIUM GIANT? - Kratka, T.; Stefl, V. (Одеські астрономічні публікації, 2007)
We were presented poster about interpretation of spectrum of the late-type lithium star HD152786 acquired within UVES Paranal Observatory Project. Using the Synspec code for synthetic spectrum calculations we obtained some physical characteristics of the star and chemical abundances of some elements including Fe and Li. We concluded that HD152786 appears to be supergiant of spectral class K3 II or K3 Ib with effective temperature Teff = 4500 K, surface gravity log g = 0.5, metallicity of [Fe/H] = -0.41 and lithium abundance of ALi = 1.15. From H-R diagram with evolutionary tracks we estimated mass of the star of (6-9)M?.